Políticas migratórias: um estudo comparado entre Brasil, Guiana Francesa e Suriname (2007-2018) - Cabral, Whitney Santos (2019)
International migration is a global phenomenon, as are the range of factors that influence the decision of increasing numbers of people to move from their home country to others. However, such displacements are not guided solely by migrant decisions, as the states of origin and destination play a decisive role in regulating their borders between those entering and leaving their territories. This phenomenon also occurs in the Amazon region, strategic scenario divided by several countries, with boundaries marked by some difficult access borders and complex regulation by the competent authorities. Based on the intense migratory flows of Brazilians in the region (which form a large community outside Brazil), as well as on the need to analyze the issue from the perspective of states, as regulatory agents capable of interfering (stimulating or restricting) migrations by Through political decisions based on their legislation, this study proposes a comparative analysis of the migratory policies applied by Brazil, France (French Guiana) and Suriname, both internally and overflowing to the regional level, that is, beyond State borders. To this end, it was initially sought to characterize the countries studied (history, politics, economy, and migration policies). Then, French, and Surinamese migratory policies were compared with those of Brazil, in order to highlight points of convergence and distinction between them. Subsequently, based on comparative methods in social sciences and migratory policies, criteria were used to measure and establish levels of comparison between the three countries on the subject. In addition to the (domestic) policies of the countries, bilateral and multilateral agreements were also analyzed, as well as the points of convergence and difference of these measures.